Shari'ah inspection of surplus distribution in Takaful operations - Soualhi, Younes (IIUM Institute of Islamic Banking and Finance, 2009)
This research tends to shed light on a member of issues to surplus distribution in Takaful. The first part would be devoted to revisiting the main financial concepts related to the surplus and profit. Modes of distribution such as pro- rata and offsetting will also be discussed in the light of equity principle advocated by Shari'ah. The second part would deal with the major juristic views and doctrines such as the ownership or otherwise of the surplus after donation would be meticulously discussed of Takaful operators. The last part would deal with a general outline of Shari'ah parameters in relation to equitable surplus distribution. This is followed by a scrutiny of surplus distribution practices of some modern Takaful operators both in Malaysia and abroad.